The domiciliary health care and its state of art: a bibliographic study - Ingrid Meireles Gomes; Luísa Canestraro Kalinowski; Maria Ribeiro Lacerda; Rosangela Martins Ferreira (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
Domiciliary care stands out since the decade of 90 as a mode which assists patient and family, understood in the social, economic and cultural contexts. Thus, this research aimed to ascertain the state of the art on domiciliary care. It is a bibliographical research about domiciliary care held between February and May/2008, in databases BDENF, LILACS, OPAS, WHOLIS, COLECIONA SUS, material from the Ministry of Health Library and complete texts at SciELO, using the terms domiciliary attendence, home care and home nursing, and the criterion for inclusion is to have content related to nursing domiciliary care, in a historical record from January 1998 to January 2008. Sixteen thematic categories were listed, of which were emphasized chronic, caregivers and elderly, totaling 103 articles examined. In these three categories stands out: health education, emphasizing the role of the nurse; profile of the caregiver; the advantages of domiciliary care outrunning the disadvantages. The researched bibliography points to the importance of the caregiver and the influence of nurses for the autonomy of the subjects; and the need for articulaton between hospital and community health services, and researches directed to the beyond biologicist vision of the health care.